Investment in human capital during incarceration and employment prospects of prisoners - Margaret Giles; Anh Tram Le (Institute for the Study of Labor (IZA), 2009)
The costs of incarceration and recidivism to the community are substantial. These costs not only include the direct costs of imprisonment but also the opportunity costs arising from depletion of human capital and loss of output. Policy makers have emphasised the importance of rehabilitating prisoners as a way of reducing recidivism. Consequently, the management of prisoners has changed, with more prisoners being encouraged to undertake some form of education, training and/or work during their incarceration in conjunction with any behavioural management programmes. This paper examines, using the 2003 Survey of Prisoners in Western Australia, the decision of prisoners to invest in education/training during their prison term and the potential labour market outcomes of this investment. The results suggest that prisoners use education/training to improve their skills in preparation for release from prison. From this perspective it can be argued that these prisoners see education/training as an investment in human capital rather than consumption. In addition, the decision to participate in either education or training is non-random and varies across the time remaining on the prison sentence, thus suggesting prisoners view education and training as different activities. However, the results show the expected benefit prisoners place on education and training is similar.
Keywords: I20; J01; J21; 330; Prisoners; education; training; employment; Straffälligenhilfe; Berufsbildung; Bildungsinvestition; Berufliche Integration; Australien